2022
DOI: 10.1097/jcma.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control was associated with nonprostate cancer and overall mortalities in diabetic patients with prostate cancer

Abstract: Background: Diabetes mellitus (DM) can worsen the prognosis or survival in prostate cancer (PC) patients. We investigated whether glycemic control impacts mortality in PC patients with existing diabetes. Methods: All PC patients with or without preexisting DM were enrolled from 2006 to 2017. Mean hemoglobin A1c (HbA1c) values (<7%, 7%-9%, ≥9%) were used to represent glycemic control. Major outcomes included all-cause, PC-specific, and non-PC mortalities. Statistical analyses were performed using Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The current study by Dr Lin also included this confounding factor-the use or no-use of metformin in PC patients with T2DM, and in their model 2 which included the use of metformin, all-cause mortality was positively correlated with poor glycemia control of T2DM and Gleason score; non-PC mortality was positively correlated with poor glycemia control of T2DM, and PC-specific mortality was positive correlated with Gleason score. 11 In conclusion, T2DM and cancer have a multifaceted relationship and may share regulatory mechanisms, although the biological links between T2DM and cancer are not completely understood. Metabolic dysregulation, dyslipidemia, hyperinsulinemia, hyperglycemia, abnormal secretion of local and systemic proinflammatory factors inducing chronic inflammation, excessive production of oxygen-free radicals through oxidative stress, abnormal levels of adipokines, such as leptin and adiponectin, overproduction of insulin-like growth factors, which are all found frequently in patients with T2DM, are also a factor in initiation, development, and progression of cancer.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The current study by Dr Lin also included this confounding factor-the use or no-use of metformin in PC patients with T2DM, and in their model 2 which included the use of metformin, all-cause mortality was positively correlated with poor glycemia control of T2DM and Gleason score; non-PC mortality was positively correlated with poor glycemia control of T2DM, and PC-specific mortality was positive correlated with Gleason score. 11 In conclusion, T2DM and cancer have a multifaceted relationship and may share regulatory mechanisms, although the biological links between T2DM and cancer are not completely understood. Metabolic dysregulation, dyslipidemia, hyperinsulinemia, hyperglycemia, abnormal secretion of local and systemic proinflammatory factors inducing chronic inflammation, excessive production of oxygen-free radicals through oxidative stress, abnormal levels of adipokines, such as leptin and adiponectin, overproduction of insulin-like growth factors, which are all found frequently in patients with T2DM, are also a factor in initiation, development, and progression of cancer.…”
mentioning
confidence: 99%
“…It is well-known that T2DM has been associated with the risk of all-site and some site-specific cancers in several systematic reviews and meta-analysis, and cancer patients (liver, endometrium, pancreas, colon, breast, gastrointestinal tract, bladder, and leukemia) with T2DM have a 15%-225% higher risk of mortality, but conflicted results have also been reported in PC. 1,2,10,12,13 Lin et al 11 showed all-cause mortality was really increased in PC patients with T2DM, regardless whether glycemic control is good or poor compared to that in PC patients without. The trend is more apparent in patients with poor glycemic control (HbA1c ≥ 9%).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, similar to many studies in the literature, the main limitation of the current article cannot avoid many confounding factors. 19,20 For example, in real-world clinical practice which is unlike to the well-established prospective, randomized clinical trial, it is hard to enroll the subjected with little heterogeneous characteristics; therefore, it is difficult to make a strong conclusion. 16 Additionally, retrospectivity in nature may also be a limit.…”
mentioning
confidence: 99%